2022
DOI: 10.1002/jcla.24443
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet distribution width‐to‐platelet ratio combined with serum thyroglobulin may be objective and popularizable indicators in predicting papillary thyroid carcinoma

Abstract: Objectives The incidence of papillary thyroid carcinoma (PTC) has increased more rapidly than that of any other cancer type in China. Early indicators with high sensitivity and specificity during diagnosis are required. To date, there has been a paucity of studies investigating the relationship between preoperative platelet distribution width‐to‐platelet count ratio (PPR) and PTC. This study thus aimed to assess the diagnostic value of PPR combined with serum thyroglobulin (Tg) in patients with PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…A few other inflammatory markers-based predictors, which have been evaluated for their reliability in DTC include, platelet distribution width (PDW), PDW-to-platelet count ratio, platelet-to-lymphocyte ratio, plateletcrit, mean platelet volume, fibrinogen, and monocyte to high-density lipoprotein cholesterol ratio. [ 10 25 34 35 36 ] Although the results have been encouraging, the calculations and interpretations of these ratios are relatively complex when compared to the NLR and LMR, making the latter ratios the most preferred.…”
Section: Discussionmentioning
confidence: 99%
“…A few other inflammatory markers-based predictors, which have been evaluated for their reliability in DTC include, platelet distribution width (PDW), PDW-to-platelet count ratio, platelet-to-lymphocyte ratio, plateletcrit, mean platelet volume, fibrinogen, and monocyte to high-density lipoprotein cholesterol ratio. [ 10 25 34 35 36 ] Although the results have been encouraging, the calculations and interpretations of these ratios are relatively complex when compared to the NLR and LMR, making the latter ratios the most preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, papillary thyroid carcinoma is the most common type, accounting for approximately 80–90% of new thyroid cancers 3 , 4 . Papillary thyroid carcinoma has a good prognosis 5 , but is prone to early lymph node metastasis 6 . It has also been shown that there is a strong relationship between lymph node metastasis and disease recurrence in PTC 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a tumor marker for PTC and an important reference for the follow‐up of patients with PTC after treatment. In recent years, more studies have shown the role of preoperative Tg in lymph node metastasis and distant metastasis 21 , 22 , 23 , 24 and the preoperative identification of follicular thyroid cancer and radioiodine refractory treatment. 25 , 26 However, fewer studies have shown the prognostic relevance of preoperative Tg to patients.…”
Section: Introductionmentioning
confidence: 99%